FAMILY SOCIAL SUPPORT AND PATIENTS MOTIVATION PREVENT PULMONARY TUBERCULOSIS TRANSMISSION - Ayu Putu Yunita Lestari; Dwi Prima Hanis Kusumaningtiyas; I Ketut Andika Priastana (Jurnal Riset Kesehatan, 2021)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis which usually attacks the lungs. The increasing number of TB patients will result in an increase in TB transmission in the community. The lack of prevention measures of TB transmission occurs because the patient has less motivation in preventing the transmission of disease. This study aims to determine the relationship of family social support with patient motivation in preventing transmission of pulmonary TB in Negara Sub-district 2019. This study is quantitative study and used a cross-sectional design. The population in this study was pulmonary TB patients in the Negara sub-district with a total sample of 43 respondents. The research sample used a Simple Random Sampling technique. Analysis of the study using Spearman’s Rho. Family social support the most lung TB people are in good category 37 (86%). The motivation of patients in preventing the transmission of the most lung TB in the category of good 40 (93%). The results of the research analysis state P = 0.005 (P = less than 0.05). There is a relationship between the social support of the family with the motivation of the patient in preventing the transmission of lung TB.